Efek Homogenisasi Spesimen Darah Metode Inversi Terhadap Nilai Hematokrit - Fadillah, Noor; Afriansyah, Muhammad Ardi; Sukeksi, Andri; Santosa, Budi (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2023)
Laboratory examination consists of three stages, namely pre-analytical, analytical, and post-analytic. The biggest error occurred in the pre-analytical stage, which was around 61%. Homogenization including the pre-analytical stage is the process of mixing blood and anticoagulants which are included in the pre-analytical stage. Homogenization has two ways namely manual and automatic. Inadequate homogenization can cause clots or rupture of erythrocytes/lysis and shrinkage of erythrocytes, leading to a falsely low hematocrit value. The study aimed to find out and analyze differences in hematocrit values by homogenizing the inversion method 2, 4, and 10 times. This type of research is observational analytic. The research was carried out in June - August 2021 at the Clinical Laboratory of Muhammadiyah University of Palangkaraya. The research sample consisted of 9 EDTA blood from 9 people according to the inclusion criteria. All samples were examined for hematocrit using a Hematology Analyzer Sysmex XP-300. The results showed that the average hematocrit value in 2 times inversion homogenization was 38.40%, 4 times homogenization was 38.78%, and 10 times homogenization was 39.14%. The conclusion of this study was that there was no significant effect of the inversion homogenization technique 2, 4, and 10 times on the hematocrit value (p=0.584 > 0.05).